A formulation approach for development of HPMC-based sustained release tablets for tolterodine tartrate with a low release variation. (November 2013) - Cao, Qing-Ri; Choi, Jae-Seung; Liu, Yan; Xu, Wei-Juan; Yang, Mingshi; Lee, Beom-Jin; Cui, Jing-Hao
<x xml:space="preserve">Abstract</x> Objective: The purpose of this study was to develop hydroxypropylmethylcellulose (HPMC)-based sustained release (SR) tablets for tolterodine tartrate with a low drug release variation. Methods: The SR tablets were prepared by formulating a combination of different grades of HPMC as the gelling agents. The comparative dissolution study for the HPMC-based SR tablet as a test and Detrusitol® SR capsule as a reference was carried out, and the bioequivalence study of the two products was also conducted in human volunteers. Results: The amount of HPMC, the grade of HPMC and the combination ratio of different grades of HPMC had remarkable effects on drug release from the SR tablets. Both the test and reference products had no significant difference in terms of comparative dissolution patterns in four different media (f2 > 50). Furthermore, the dissolution method and rotation speed showed no effects on the drug release from the two products. The 90% confidence intervals of the AUC0–36 and Cmax ratios for the test and reference products were within the acceptable bioequivalence intervals of log0.8–log1.25. Conclusions: A HPMC-based SR tablet for tolterodine tartrate with a low release variation was successfully developed, which was bioequivalent to Detrusitol® SR capsule.